Aquafilling Filler for Buttock Augmentation Cause Severe Long-Term Complications: A Case Report - Camilla Soendergaard Kristiansen; Christian Lyngsaa Lang; Ann Haerskjold; Claus Zachariae; Anders Klit (Indian Journal of Plastic Surgery)
Filler injections for buttock augmentation are becoming more popular as a cosmetic procedure, which leads to an expected increase in the number of complications emphasizing the importance of reporting cases with both well-known, severe, and previously undiscovered complications, as well as their possible treatment strategies.